2014
DOI: 10.11648/j.ajns.20140302.11
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Knowledge among Female Adolescents in Egypt

Abstract: Abstract:Osteoporosis is a growing chronic health problem that could result in mortalities and poor living quality.Although osteoporosis is a preventable disease affecting millions of people, the public awareness remains low and the most effective prevention of this disease is founded during childhood and adolescence when the prevention is actually the easiest. Aim: The current study assessed osteoporosis knowledge among female adolescents students in selected secondary school at El-Minia, Egypt. Methods: Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Women are more likely to develop osteoporosis than men for 3 main reasons, first, women normally have a lower peak bone mass than men, second, women experience an accelerated loss of bone following the hormonal changes associated with menopause and third, women generally live longer than men so they continue to experience the bone loss associated with aging for a longer time [12], for these reasons women need to be more educated regarding osteoporosis especially before menopause. In this study 44.4% correctly define osteoporosis which was higher than findings of study (36.6%) in Egypt [13].…”
Section: Discussioncontrasting
confidence: 71%
“…Women are more likely to develop osteoporosis than men for 3 main reasons, first, women normally have a lower peak bone mass than men, second, women experience an accelerated loss of bone following the hormonal changes associated with menopause and third, women generally live longer than men so they continue to experience the bone loss associated with aging for a longer time [12], for these reasons women need to be more educated regarding osteoporosis especially before menopause. In this study 44.4% correctly define osteoporosis which was higher than findings of study (36.6%) in Egypt [13].…”
Section: Discussioncontrasting
confidence: 71%
“…Exercising on a regular basis is less likely to get osteoporosis was agreed by the majority of the study subjects (Table 7). This is supported of a research by [48] who studied "Osteoporosis knowledge among female adolescents in Egypt". They reported that "students knew that regular exercise can protect against osteoporosis, but this knowledge does not translate to practices; nearly one-half of the students were exercising at a minimal level and not on regular basis".…”
Section: Research Question No2 What Are the Preventive Measures Awarmentioning
confidence: 53%
“…4). This is supported by a study by [48] who studied "Osteoporosis knowledge among female adolescents in Egypt" and stated that most of their participants identified regular exercise as a preventive measure for osteoporosis and were aware of the benefits of exercise in preventing osteoporosis.…”
Section: Research Question Nomentioning
confidence: 79%
“…In a study by Hammoudeh et al, low calcium intake (96.7%), older age (89.5%) and a family history of osteoporosis (86.0%) were the most commonly selected [43]. Egyptian respondents most frequently indicated female gender (48.4%), older age (29.8%) and low calcium content in the diet (5.7%) [44]. In our own study, the following were most often indicated: older age (50.5%), calcium deficiency in the diet (46.6%) and consumption of large amounts of tea and coffee (42.4%), while menopause was relatively rarely associated with this disease (22.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above results, it can be concluded that osteoporosis is associated in society with being elderly and following a diet low in calcium. A relatively small percentage of respondents also associated cigarette smoking and caffeine consumption with osteoporosis [38,42,44].…”
Section: Discussionmentioning
confidence: 99%